2022
DOI: 10.3389/fnins.2022.801774
|View full text |Cite
|
Sign up to set email alerts
|

Brain functional connectivity analysis in patients with relapsing-remitting multiple sclerosis: A graph theory approach of EEG resting state

Abstract: Multiple sclerosis (MS) is an autoimmune disease related to the central nervous system (CNS). This study aims to investigate the effects of MS on the brain's functional connectivity network using the electroencephalogram (EEG) resting-state signals and graph theory approach. Resting-state eyes-closed EEG signals were recorded from 20 patients with relapsing-remitting MS (RRMS) and 18 healthy cases. In this study, the prime objective is to calculate the connectivity between EEG channels to assess the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Similarly, Babiloni et al 55 found that alpha and delta activities in the resting state were lower in PwMS. Conversely, an increase in alpha and gamma was found in 57 . Keune et al showed a correlation between increased alpha 1 and 2 activity, as well as increased frontal theta\beta ratio with worse performance in the symbol digit modalities test (SDMT) test for MS 53 .…”
Section: Eeg and Evoked Potentialsmentioning
confidence: 83%
“…Similarly, Babiloni et al 55 found that alpha and delta activities in the resting state were lower in PwMS. Conversely, an increase in alpha and gamma was found in 57 . Keune et al showed a correlation between increased alpha 1 and 2 activity, as well as increased frontal theta\beta ratio with worse performance in the symbol digit modalities test (SDMT) test for MS 53 .…”
Section: Eeg and Evoked Potentialsmentioning
confidence: 83%
“…Similarly, Babiloni et al 55 found that alpha and delta activities in the resting state were lower in PwMS. Conversely, an increase in alpha and gamma was found in 57 . Keune et al showed a correlation between increased alpha 1 and 2 activity, as well as increased frontal theta\beta ratio with worse performance in the 3/17 symbol digit modalities test (SDMT) test for MS 53 .…”
Section: Eeg and Evoked Potentialsmentioning
confidence: 83%
“…They revealed an inverse correlation between the P300 amplitude and the fatigue level. Furthermore, evoked potentials in EEG have been analyzed during resting state [51][52][53][54][55][56][57][58][59][60] , during attention tasks [61][62][63][64] or motor tasks 42 . Authors in 11 showed that a combination of evoked potentials (EPs) could predict MS progression in terms of Expanded Disability Status Scale (EDSS) after 20 years.…”
Section: Eeg and Evoked Potentialsmentioning
confidence: 99%